Depression Suppresses Treatment Response for Traumatic Loss-Related PTSD in Active Duty Military Personnel - Jacoby, Vanessa M. (J Trauma Stress, 2019)
There are multiple well-established evidence-based treatments for posttraumatic stress disorder (PTSD). However, recent clinical trials have shown that combat-related PTSD in military populations is less responsive to evidence-based treatments than PTSD in most civilian populations. Traumatic death of a close friend or colleague is a common deployment-related experience for active duty military personnel. When compared with research on trauma and PTSD in general, research on traumatic loss suggests that it is related to higher prevalence and severity of PTSD symptoms. Experiencing a traumatic loss is also related to the development of prolonged grief disorder, which is highly comorbid with depression. This study examined the relationship between having traumatic loss-related PTSD and treatment response to Cognitive Processing Therapy in active duty military personnel. Participants included 213 active duty service members recruited across two randomized clinical trials. Results showed that service members with primary traumatic loss-related PTSD (n = 44) recovered less from depressive symptoms than those with different primary traumatic events (n = 169). Tests of mediation found that less depression recovery suppressed recovery from PTSD symptoms in those with traumatic loss-related PTSD. These findings suggest that evidence-based treatments for PTSD should better accommodate loss and grief in military populations.